STUDIUL MODIFICĂRILOR HEMATOLOGICE ÎN DIABETUL ALLOXANIC PE FONDUL FITOTERAPIEI - Gherman, Ion (CEP USM, 2011)
Diabetes is conditioned by the total or partial absence of insulin in human body, which is elaborated by the β-cellarof pancreas endocrine. The results obtained in our research permitted to mention that the extracts from a complex of medicinal plants (Equisetum arvense, Arctium lappa, Tilia, Verbascum phlomoides) have on essential action on the functional state of the which is expressed by a normalization tendency of the pancreas hormonal state.
Keywords: diabet zaharat; diabet alloxanic; plante medicinale.